Business partnership essentials : a step-by-step action plan for succeeding in business with a partner - Lehavi, Dorene (Walter de Gruyter, Inc., 2018)
"Business partnerships are vital to the US economy yet their failure rate is alarming: 70% of them don't make it. Dr. Lehavi is leading the charge to reverse this statistic. As a business partnership relationship coach, she intimately knows the impact that these partnerships have on cofounders, employees, customers, families, local communities, and global markets. Business partnership essentials walks you through every phase of the process--from choosing the right partner and operating your business on a daily basis, all the way through to exit and planning for the unexpected. This book is not a book on business startups and so it does not address the finances of starting up a partnership, but rather, it focuses on agreeing on all aspects of your relationship with your business partner. Following Lehavi's guidance will ensure that you've done everything you can to help your partnership succeed"--EBSCO pdf information screen